Association of lifestyle factors with mortality risk in people with chronic obstructive pulmonary disease: a prospective cohort study - Zhang, Yue; Ren, Yue; Li, Zhenhua; Yu, Yaohua; Xu, Xia; Ye, Jianping; Zhang, Hua (Frontiers in Medicine, 2025)
BackgroundWhich lifestyle will benefit patients with chronic obstructive pulmonary disease (COPD) has becoming a hot topic in recent years. However, there are currently no recommendations. Life’s Essential 8 (LE8) includes 8 metrics (BMI, non-HDL cholesterol, blood pressure, blood glucose, physical activity, diet, sleep duration, and nicotine exposure), which are considered the foundation of maintaining a healthy life. Here, we aimed to explore the relationship between LE8 and mortality risk in patients with chronic obstructive pulmonary disease (COPD), which may provide advice on how to live better for these patients.MethodsParticipants were from the National Health and Nutrition Examination Survey 2003–2018 at baseline linked to the 2019 National Death Index records. Cox proportional hazards regression models were used to explore the relationship between the LE8 score and mortality risk. All analyses were adjusted for survey design and weighting variables.ResultsWe included 1,593 participants with COPD, representing 9,208,187 US patients. During a median follow-up of 5.8 years, compared with patients with low LE8 scores, those with moderate and high score presented decreased all-cause mortality (both log-rank p < 0.05) and increased 10-year survival rates (63.6, 72.4 and 89.9%, respectively). Patients in the high (HR 0.19, 95% CI 0.09–0.40) and moderate (HR 0.61, 95% CI 0.43–0.86) score groups had a lower risk of all-cause mortality after adjusted for confounders. Similar results were observed in high (HR 0.53, 95% CI 0.32–0.88) and moderate (HR 0.68, 95% CI 0.50–0.91) HB score groups. Among the 8 metrics, physical activity, sleep health, nicotine exposure and blood glucose were important contributors to decreased mortality risk. And there were approximately linear dose–response relationships between LE8 and HB score with all-cause mortality risk.ConclusionThe LE8 score was inversely associated with all-cause mortality risk of patients with COPD. Changing lifestyles to improve LE8 scores may be an effective strategy to benefit these patients.